THE EFFECTIVENESS OF TELE-REHABILITATION VERSUS IN-PERSON THERAPY FOR CHRONIC MUSCULOSKELETAL PAIN MANAGEMENT (Vietnam Journal of Community Medicine, 2026)
Chronic musculoskeletal (MSK) pain represents a profound and escalating global health burden, traditionally managed almost exclusively through conventional, in-person physiotherapy. However, the rapid digital transformation of healthcare, catalyzed significantly by the COVID-19 pandemic, has positioned tele-rehabilitation as a critical and scalable alternative. This critical review aims to evaluate the clinical efficacy, biomechanical outcomes, and psychosocial dimensions of tele-rehabilitation compared to traditional face-to-face therapy for chronic MSK pain management. Utilizing a systematic synthesis methodology guided by the PICOS framework, this study critically analyzed a finalized cohort of 38 high-level studies, comprising 24 randomized controlled trials and 14 systematic reviews or meta-analyses. The extracted data consistently indicates that for active interventions, such as therapeutic exercise, postural correction, and strength training, tele-rehabilitation is clinically non-inferior to face-to-face care. Significant improvements were observed across complex pathologies, including chronic neck pain, forward head posture, low back pain, and lower extremity osteoarthritis. Furthermore, the results demonstrate that remote diagnostic assessments maintain remarkably high validity and inter-rater reliability, provided that strict, standardized operational protocols are systematically followed. The synthesis also highlights that the long-term success of these digital care models relies heavily on a fundamental restructuring of clinical pedagogy; specifically, the integration of innovative technologies into teaching and learning environments is required to develop robust digital competencies for future clinicians. While acknowledging persistent systemic barriers, including disparities in digital health literacy and the inherent lack of hands-on manual therapy, this review confirms that tele-rehabilitation represents a highly effective, empowering, and essential paradigm for modern MSK pain management.
Keywords: Tele-rehabilitation; Musculoskeletal Pain; Physical Therapy; Digital Health; Forward Head Posture; Medical Informatics; Therapeutic Exercise.